A Proficiency-Based Progression Simulation Training Curriculum to Acquire the Skills Needed in Performing Arthroscopic Bankart and Rotator Cuff Repairs—Implementation and Impact - Angelo, Richard L.; St Pierre, Pat; Tauro, Joe; Gallagher, Anthony G.; Barber, Alan; Beach, William; Burns, Joseph; Caldwell, Paul; Curtis, Alan; Dodds, Julie; Field, Larry; Leland, Marty; et al. (Arthroscopy, 2021)
To investigate the impact of a proficiency-based progression (PBP) curriculum employed to teach trainees in the skills needed to demonstrate proficiency for an arthroscopic Bankart repair (ABR) and an arthroscopic rotator cuff repair (ARCR) by objectively comparing pre- and immediate postcourse performances. In a prospective study, 16 arthroscopy/sports medicine fellows and 2 senior residents (complete group: N = 18) were randomly assigned to perform a precourse cadaveric ABR (Bankart subgroup: N = 6), ARCR (cuff subgroup: N = 6), or basic skills on a shoulder simulator (N = 6). After completing a PBP training curriculum, all 18 registrants performed both an ABR and ARCR scored in real time by trained raters using previously validated metrics. The Bankart subgroup made 58% fewer objectively assessed errors at the completion of the course than at baseline (P = .004, confidence interval –1.449 to –0.281), and performance variability was substantially reduced (standard deviation = 5.89 vs 2.81). The cuff subgroup also made 58% fewer errors (P = .001, confidence interval –1.376 to 0.382) and showed a similar reduction in performance variability (standard deviation = 5.42 vs 2.1). Only one subject’s precourse baseline performance met the proficiency benchmark compared with 89% and 83% of the all registrants on the final ABR and ARCR cadaveric assessments, respectively. The results of this study reject the null hypothesis. They demonstrate that the implementation of a PBP simulation curriculum to train the skills necessary to perform arthroscopic Bankart and rotator cuff repairs results in a large and statistically significant improvement in the trainee’s ability to meet the 2 related performance benchmarks. Proficiency was demonstrated by 89% and 83% of the trainees for an ABR and an ARCR, respectively, in a two- and one-half day course. Surgical training employing a PBP curriculum is efficient, effective, and has the potential to improve patient safety.